Implicit and explicit attitudes toward gay men and lesbian women among heterosexual undergraduate and graduate psychology and nursing students - Hamtzani, Oz; Mama, Yaniv; Blau, Ayala; Kushnir, Talma (Frontiers in Psychology, 2022)
Objectives: To examine implicit and explicit attitudes toward gay men and lesbian women among heterosexual undergraduate and graduate psychology and nursing students. Methods: Implicit attitudes were measured via the Implicit Association Test and explicit attitudes via the Attitudes Toward Lesbian Women and Gay questionnaire. Main results: All groups held negative implicit attitudes toward gay men and lesbian women. Among undergraduates, nursing students reported holding more negative explicit attitudes toward gay men and lesbian women than psychology students. Conclusions: The curricula in both nursing and psychology studies need to address the medical and paramedical needs and issues of sexual minorities.